DETERMINANT FACTORS OF MOBILE BANKING USAGE: CASE STUDY IN KUPANG, EAST NUSA TENGGARA - Hedwig H. T. Lejap; Maria Augustin Lopes Amaral; Selfiana Goetha; Engelbertus G. Ch. Watu; Apryanus Fallo (Riset Ekonomi Pembangunan, 2021)
A review of previous research on m-banking in developing countries reveals that research on the drivers of trust in mobile banking is somewhat limited. Therefore, this study attempts to investigate the factors that influence the user's perception of confidence in mobile banking services. This model was tested empirically using an online survey from a convenience sampling of 95 respondents and analyzed using SEM PLS. This study estimates that six variables (perceived credibility, perceived benefits, security risks, privacy risks, social influence, and perceived behavioral control) directly impact perceived trust in mobile banking. The results, in particular, perceived benefits positively affect perceived trust in mobile banking, followed by social influence, security risk, and privacy risk has power on perceived trust in mobile banking. On the other hand, perceived credibility and PBC show no significant effect on the belief of mobile banking users.